Isolation and evaluation of antioxidants from leaves of Uvaria rufa (Dunal) Blume – Annonaceae - Trần, Thị Minh Tâm; Huỳnh, Ngọc Thuỵ (Hue University Journal of Science: Natural Science, 2024)
Uvaria rufa (Dunal) Blume is exclusively utilized for postpartum women in certain traditional medicine hospitals. This study was carried out to isolate the compounds with antioxidant effects in the leaves to use this medicinal plant more effectively. Extraction, seperation, isolation and purification were done as routine work. Structure elucidation was based on ultraviolet spectroscopy, mass spectrometry (MS) and nuclear magnetic resonance (NMR) spectroscopy methods. The in vitro antioxidant activity of isolated compounds was performed on DPPH (2,2- diphenyl-1-picrylhydrazyl) free radical quenching method on 96 well plates. From ethyl acetate fraction, 2 compounds, ie. isoquercitrin and rutin were isolated, exhibited antioxidant activity with IC50 values of 3.33 µM and 16.42 µM, respectively. These results will be the basis for further testing of other biological activities of the plant.